Patches, Silos, Networks: Women's Ways of Leading in South African Fisheries Value Chains - Fonto, Lauren (Social Anthropology, 2022)
Women's contributions to fisheries have often been made invisible. Their leadership in general and in fisheries has also not always been recognised, especially if it is informal or more "behind-the-scenes". The aim of this study is to contribute to the gap in the women and fisheries literature on what leadership roles women play in the South African fisheries value chain. While it is more widely known that women play diverse roles within the fisheries value chain, the leadership roles they play (at various scales) are currently less well-known. This research involved finding women to interview from the various "patches" in the value chain. Without the generation of new relationships/leads occurring in the background, it would not have been possible to find particular patches. When the research was pivoted to digital research due to the Covid-19 pandemic, the "patches" seemed more adrift, and possibly more "siloed", than ever. However, three common threads emerged that showed how these patches are not so isolated after all. The threads were: Networks and relationships; lineage, blood and sustainability; and acts of pioneering, innovating and self-empowerment. Interviews were semi-formal, with most in-person, one done via the messaging service WhatsApp, and one done via email. Digital research consisted of collecting Instagram posts, finding relevant news articles, looking at newsletters, and industry body-related media. Women in fisheries are situated within various networks and "patches" of knowledge. This dissertation has drawn on the notion of "patches" as a central concept. Underlying this were the sub-themes of gender and market access (in this case, markets for marine resources). It is clear that while different women in different patches may not necessarily know each other or interact with each other, the patches themselves still have an effect on each other. This is especially true in the case of how the Covid-19 pandemic affected small-scale fisheries. Effects higher up the value chain meant that small-scale fishers were negatively affected. Thus, fishing industry patches do not seem to exist in silos. Specifically, women in the fisheries value chain are not in silos either. Both print and online media can still allow women to find out where women are working in the value chain, and for which companies or organisations. Such media can also allow women in fisheries to develop knowledge about each other. Firstly, technology, including digital newsletters, allows for women to extend themselves and enrich themselves with relationships with or knowledges of, other people. With the proliferation of both online media and cell phone access in South Africa, parasocial relationships may be formed. These parasocial relationships may help women in fishing to know "who's who" and also for consumers desiring a more transparent buying experience to form a type of relationship with each other, through learning about people's stories. Fishers encountered both in real life and online tended to come from a long history of working in fisheries themselves, as well as coming from multi-generational fishing families. While not all of the women interviewed are leaders in formal positions and/or formal organisations, their knowledge of species, fish processing and other areas was something that seemed to be valued within fisheries-related spaces. This is one factor that indicates the importance of keeping the fishing lineage going into the future for fishers. Fishers were also concerned about the effects on them which were caused by changes at the commercial level, such as a decline in market access due to Covid-19. Keeping a fishing livelihood going, both for this generation and the next, is something very important to the fishers encountered throughout this research. The diversity of jobs women held, both those personally interviewed and those interviewed in digital publications, was significant throughout this research. Some women are in supportive spaces that allow them to pioneer new paths for women in the fishing engineer, such as being a boat skipper or engineer. Women are gradually making their way up through middle management and to executive management levels. However, it is also important to consider the intersections of women's identities, e.g. socioeconomic status, geographic location, and education obtained. Different approaches to empower different groups of women can help the process of women's empowerment in fisheries to be inclusive.